Idiolek Penggunaan Bahasa Melayu Patani Selatan ke Bahasa Indonesia - Juliana; Amelia, Witra (J-LELC: Journal of Language Education, Linguistics, and Culture, 2023)
This study aims to describe how the forms of idiolects used by Thai students in communicating and analyze how the idiolect forms of Thai Patani Malay language against Indonesian. This study uses a qualitative description method. The object of this study is the idiolect used by Thai students using spoken techniques (interviews). Data obtained by using the method of observing, recording and noting. The results of the research conducted, the two students verbally communicated quite well. In understanding, what they convey can be understood. However, from a linguistic point of view, especially in the field of phonology, there are still mistakes that must be corrected, especially Hamdi Bin Ismail. Their pronunciation in speaking using Indonesian is still experiencing difficulties, so there are frequent pronunciation errors. The mistake that is often made is removing the final phoneme and changing the phoneme /a/ to phonemes /o/ and /e/. Occasionally they also omit the phoneme /r/, because they have difficulty pronouncing the phoneme /r/ clearly. Mistakes that occur, due to a lack of mastery of using the Indonesian language, as well as a lack of confidence, and not wanting to socialize with Indonesian people, both friends on campus and the community around where they live.